Manufacturing method of ultraviolet light receiving element
Patent Information
- Application Number
- JP2021018406
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-08
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-02-08
AI Technical Summary
【0008】 本開示の一態様によれば、得られる光電流量を増大させて、より高い受光感度を有する紫外線受光素子の製造方法を得ることができる。
Smart Images

Figure 0007633034000002 
Figure 0007633034000003 
Figure 0007633034000004
Abstract
Description
Technical Field
[0001] The present disclosure relates to an ultraviolet light receiving element and a method for manufacturing the ultraviolet light receiving element.
Background Art
[0002] As an example of an ultraviolet light receiving element, an ultraviolet light receiving element that is a p-type gate photofet (Field Effect Transistor) using a GaN / AlGaN heterostructure is known (see, for example, Patent Document 1).
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] In the above-described ultraviolet light receiving element, when light is incident on the element, it is difficult to obtain a current (photocurrent) that is greater than the current flowing through the two-dimensional electron gas generated between the first nitride semiconductor layer and the second nitride semiconductor layer.
[0005] The present disclosure aims to obtain a method for manufacturing an ultraviolet light receiving element that increases the obtained photocurrent and has higher light reception sensitivity. Purple
Means for Solving the Problems
[0006] The surface of the second nitride semiconductor layer is plasma-etched with a mixed gas of BCl 3gas and SF 6 gas for 200 seconds or more and 300 seconds or less, so that the density is 1.0×10 13 cm -2 or more and 1.0×10 14 cm -2 or less It is characterized by comprising a capture level forming step of forming a capture level, and an electrode forming step of depositing a source electrode and a drain electrode on a second nitride semiconductor layer.
[0007] Also, an ultraviolet light receiving element according to another embodiment of the present disclosure Manufacturing method is , after forming A on a plate on the substrate l X Ga (1-X) a first nitride semiconductor layer containing N(0.45≦X≦0.8) , and then forming A on the first nitride semiconductor layer on the substrate l Y Ga (1-Y) a second nitride semiconductor layer containing N(X<Y≦1.0) to form a laminate having the first nitride semiconductor layer and the second nitride semiconductor layer A laminate forming step; by etching the surface of the second nitride semiconductor layer by immersing it in an acidic solution at 100° C. in which sulfuric acid and hydrogen peroxide solution are mixed in a range of 1:2 to 2:1 for 10 minutes, a capture level with a density of 1.0×10 13 cm -2 or more and 1.0×10 14 cm -2 or less A capture level forming step of forming and on the second nitride semiconductor layer 、 a source electrode and a drain electrode An electrode forming step of forming by vapor deposition and is characterized by comprising the same. Further, a method for manufacturing an ultraviolet light receiving element according to another embodiment of the present disclosure includes forming a first nitride semiconductor layer containing Al X Ga (1-X) N (0.45≦X≦0.8) on a substrate, and then forming a second nitride semiconductor layer containing Al Y Ga (1-Y) N (X<Y≦1.0) on the first nitride semiconductor layer to form a laminate having the first nitride semiconductor layer and the second nitride semiconductor layer; and annealing the substrate and the laminate at 1100° C. in a hydrogen atmosphere to form a capture level having a density of 1.0×10 13 cm -2 or more and 1.0×10 14 cm -2 or less on the surface of the second nitride semiconductor layer; and an electrode forming step of forming a source electrode and a drain electrode by vapor deposition on the second nitride semiconductor layer.
Advantages of the Invention
[0008] According to one aspect of the present disclosure, the obtained photocurrent amount is increased to have a higher light receiving sensitivityPurple A method for manufacturing an infrared light receiving element can be obtained. [Brief description of the drawings]
[0009]
FIG. 1
FIG. 2
FIG. 3
[0010] The ultraviolet light receiving element according to the present embodiment will be described below through the embodiments, but the following embodiments do not limit the invention according to the claims. Also, not all of the combinations of features described in the embodiments are necessarily essential to the solution of the invention.
[0011] 1. Functions and Effects of the UV-Receiving Element Disclosed Herein The ultraviolet light receiving element according to the present disclosure includes a first nitride semiconductor layer and a second nitride semiconductor layer formed in this order on a substrate. As a result, a two-dimensional electron gas is generated at the interface between the first nitride semiconductor layer and the second nitride semiconductor layer. In addition, a trap level is formed in the laminate of nitride semiconductor layers (particularly the surface or inside of the second nitride semiconductor layer) by etching the surface of the second nitride semiconductor layer (the surface of the second nitride semiconductor layer opposite to the first nitride semiconductor layer) with plasma or an acidic solution, or by annealing at a predetermined temperature in a hydrogen atmosphere. By forming optimal source and drain electrodes on such a laminate of nitride semiconductor layers (second nitride semiconductor layer), the layer of the two-dimensional electron gas can be depleted.
[0012] As a result, when ultraviolet light that should be incident on the ultraviolet light receiving element is not incident (dark state), the current through the two-dimensional electron gas is suppressed, and the current (dark current) can be suppressed. On the other hand, when ultraviolet light that should be incident on the ultraviolet light receiving element is incident, the light absorbed in the depletion layer (corresponding to the band gap of the first nitride semiconductor layer) is converted into electrons and extracted as a current by the electric field between the source electrode and the drain electrode. At this time, the electrons of the two-dimensional electron gas are also obtained as a current, so a high photocurrent is obtained. Furthermore, carriers (e.g., holes) are excited in the stack of nitride semiconductor layers (particularly the second nitride semiconductor layer) by irradiation with ultraviolet light. These carriers are captured by the capture level formed in the stack of nitride semiconductor layers.
[0013] The captured carriers are accumulated by the density of the capture levels, and when the carriers are holes, they have the effect of inducing electrons. That is, in addition to the current obtained by the two-dimensional electron gas, a current is also obtained by the carriers captured by the capture levels. Since the density of the capture levels formed in the ultraviolet light receiving element according to the present disclosure is comparable to the two-dimensional electron gas concentration, the ultraviolet light receiving element can obtain a photocurrent higher than the current flowing through the two-dimensional electron gas. In general, in electronic devices, the density of the capture levels is required to be reduced because they hinder the movement of carriers. On the other hand, in the ultraviolet light receiving element according to the present disclosure, the capture levels show the effect of obtaining a high photocurrent.
[0014] Due to these mechanisms, the ultraviolet light receiving element according to the present disclosure responds only to light with wavelengths of 190 nm to 290 nm (ultraviolet light), has a low dark current, and, for example, a 10 μW / cm 2 As a result, the ultraviolet light receiving element according to the present disclosure has a high S / N ratio (ratio of the photocurrent value to the dark current value, 6.0×10 5 More preferably, 1.0×10 6 ) and high light receiving sensitivity (10 5 This will enable the realization of both the above and A / W.
[0015] 2. Structure of UV light receiving element An ultraviolet light receiving element according to an embodiment of the present disclosure will be described. The ultraviolet light receiving element includes a substrate, and a first nitride semiconductor layer disposed on the substrate and containing Al X Ga (1-X) N (0.45 ≦ X ≦ 0.8), and a laminate having a second nitride semiconductor layer disposed on the first nitride semiconductor layer and containing Al Y Ga (1-Y) N (X < Y ≦ 1), and a source electrode and a drain electrode disposed on the second nitride semiconductor layer. Further, the ultraviolet light receiving element has a trapping level with a density of 1.0 × 10 11 cm -2 or more and 1.0 × 10 14 cm -2 or less in either the first nitride semiconductor layer or the second nitride semiconductor layer. Hereinafter, each layer will be described in detail.
[0016] (Substrate) The substrate can be any material that can be used as a semiconductor substrate, and a nitride semiconductor substrate containing a nitride semiconductor such as an AlN single crystal substrate or an AlGaN substrate, a sapphire substrate, etc. can be used. Further, as the substrate, a laminated substrate in which an AlN layer is disposed on an AlN single crystal substrate or a sapphire substrate may be used.
[0017] Here, in the expression "nitride semiconductor substrate containing a nitride semiconductor", "containing" means mainly containing a nitride semiconductor in the layer, but this expression also includes the case of containing other elements. Specifically, this expression also includes the case where a slight change is made to the composition of this layer by adding a small amount of an element other than the nitride semiconductor (for example, several% or less of an element such as Ga (when Ga is not the main element), In, As, P, or Sb). In the expressions of the compositions of other layers, the term "containing" has the same meaning. Also, the small amount of elements contained is not limited to the above.
[0018] (First Nitride Semiconductor Layer) The first nitride semiconductor layer is formed on a substrate. Here, for example, the wording "on" in the expression "the first nitride semiconductor layer is formed on a substrate" means that the first nitride semiconductor is formed on one surface of the substrate. The above expression also includes the case where another layer is present between the substrate and the first nitride semiconductor layer. The wording "on" has the same meaning in the relationship between other layers. For example, the expression "the second nitride semiconductor layer is formed on the first nitride semiconductor layer" also includes the case where a composition gradient layer is provided between the first nitride semiconductor layer and the second nitride semiconductor layer. The first nitride semiconductor layer forms a stack together with the second nitride semiconductor layer described later.
[0019] The first nitride semiconductor layer is, for example, Al X Ga (1-X) N (0.45≦X≦0.8). This makes it possible to emit (receive) a signal only when light in the ultraviolet region is irradiated onto the ultraviolet light receiving element. By increasing the Al composition ratio X of the first nitride semiconductor layer, the Al composition ratio Y of the second nitride semiconductor layer also increases, and the contact resistance to the ultraviolet light receiving element increases. From the viewpoint of electrode contact to the ultraviolet light receiving element, the first nitride semiconductor layer is preferably Al X Ga (1-X) N (0.45≦X≦0.6).
[0020] The first nitride semiconductor layer may contain impurities such as Group V elements other than N, such as In, P, As, and Sb, and impurities such as C, H, F, O, Mg, and Si, but the types of impurity elements are not limited to these. From the viewpoint of lattice relaxation within the first nitride semiconductor layer, the first nitride semiconductor layer preferably has a layer thickness of 50 nm to 500 nm, more preferably 100 nm to 300 nm. Here, "lattice relaxation within the first nitride semiconductor layer" means that the a-axis lattice constant at the upper end surface of the first nitride semiconductor layer is larger than the a-axis lattice constant at the lower end surface of the first nitride semiconductor layer.
[0021] (Second nitride semiconductor layer) The second nitride semiconductor layer is formed on the first nitride semiconductor. As described above, the second nitride semiconductor layer forms a laminate together with the first nitride semiconductor layer. The second nitride semiconductor layer is, for example, Al X Ga (1-X) N (X < Y < 1). Thus, when light in the ultraviolet region irradiates the ultraviolet light receiving element, a two-dimensional electron gas is generated at the interface between the first nitride semiconductor layer and the second nitride semiconductor layer, making it possible to obtain an extremely high photocurrent. The second nitride semiconductor layer may contain group V elements other than N such as In, P, As, and Sb, and impurities such as C, H, F, O, Mg, and Si, but the types of impurity elements are not limited to this.
[0022] (Trapping level) The trapping level may be present at any location of the ultraviolet light receiving element. As described above, the trapping level is formed in either the laminate, that is, either the first nitride semiconductor layer or the second nitride semiconductor layer. The trapping level preferably exists on the surface or in the film of the laminate (the first nitride semiconductor layer and the second nitride semiconductor layer). Here, for example, the term "surface" in the expression "exists on the surface or in the film" means that it may be formed on the entire surface of the layer or only a part thereof. Also, the term "in the film" means that it may be uniformly formed in the film or only formed in a part thereof. Also, a structure in which the trapping level is formed at the interface between the first nitride semiconductor layer and the second nitride semiconductor element is also included in the above expression.
[0023] From the viewpoint of obtaining a high photocurrent, the density of the trapping level is 1.0×10 11 cm -2 or more and 1.0×10 14 cm -2 or less, and preferably 1.0×10 12 cm -2 or more and 1.0×10 14 cm -2 or less. From the viewpoint of obtaining a higher photocurrent than the effect of the two-dimensional electron gas, the density of the trapping level is 1.0×1013 cm -2 Above 1.0×10 14 cm -2 It is more preferable that: From the viewpoint of the formation of trap levels and the induction of electrons by the accumulated carriers, it is more preferable that the trap levels are present on the surface or in the film of the second nitride semiconductor layer.
[0024] The concentration of the two-dimensional electron gas generated between the first nitride semiconductor layer and the second nitride semiconductor layer is determined by the Al composition ratio X of the first nitride semiconductor layer, the Al composition ratio Y of the second nitride semiconductor layer, and the film thickness t of the second nitride semiconductor layer. The carrier concentration of the two-dimensional electron gas can be calculated as an actual measured value by Hall measurement or C-V measurement, but it can be calculated more simply from the structure of each layer using software such as SiLENSe (manufactured by STR) or Atlas (manufactured by Silvaco).
[0025] In an ultraviolet light receiving element, the higher the concentration of the two-dimensional electron gas generated, the higher the photocurrent that can be obtained when irradiated with ultraviolet light. On the other hand, in an ultraviolet light receiving element, the higher the concentration of the two-dimensional electron gas generated, the higher the dark current that flows even in a dark state. Therefore, in order to obtain a high photocurrent, the first nitride semiconductor layer and the second nitride semiconductor layer have suitable values in their configurations. For this reason, the first nitride semiconductor layer and the second nitride semiconductor layer are preferably configured so that the Al composition ratio X of the first nitride semiconductor layer, the Al composition ratio Y of the second nitride semiconductor layer, and the film thickness t [nm] of the second nitride semiconductor layer satisfy the following formula (1). When the configuration of the first nitride semiconductor layer and the second nitride semiconductor layer satisfies formula (1), an ultraviolet light receiving element with a high S / N ratio, which is the ratio of the photocurrent value to the dark current value, can be obtained. -0.009×t+X+0.25≦Y≦-0.009×t+X+0.45···(1)
[0026] (electrode) A source electrode and a drain electrode are formed on the second nitride semiconductor layer. There are no limitations on the material for forming the source electrode and the drain electrode, so long as it can form a sufficient depletion layer by Schottky junction with the second nitride semiconductor layer in the dark (MSM type) to suppress dark current, and has a sufficiently low barrier for extracting photocurrent via the two-dimensional electron gas when irradiated with ultraviolet light. A material that satisfies these conditions preferably contains Al, Au, and at least one of V, Ti, Zr, Rh, Mo, Ni, Pt, Pd, W, and Ta, and is particularly preferably an alloy containing V, Al, Mo, and Au.
[0027] The source electrode and the drain electrode are, for example, stacked electrodes formed of a V layer having a thickness of 10 nm to 30 nm, an Al layer having a thickness of 70 nm to 90 nm, an Mo layer having a thickness of 30 nm to 50 nm, and an Au layer having a thickness of 40 nm to 60 nm, which are successively formed on the second nitride semiconductor layer.
[0028] There is no limitation on the size (length, width) and shape of the source electrode and the drain electrode. For example, the source electrode and the drain electrode may each be rectangular and arranged facing each other on the surface of the second nitride semiconductor layer, or may be comb-shaped. From the viewpoint of the formation of a depletion layer due to a Schottky barrier between the second nitride semiconductor layer and the width of the depletion layer, the distance between the source electrode and the drain electrode is preferably 1.0 μm or more and 30 μm or less. Furthermore, from the viewpoint of chip size, the distance between the source electrode and the drain electrode is more preferably 1.0 μm or more and 15 μm or less.
[0029] The ultraviolet light receiving element may have a gate electrode between the source electrode and the drain electrode. Here, for example, the word "between" in the expression "between the source electrode and the drain electrode" means that the gate electrode may be present over the entire area between the source electrode and the drain electrode, or may be present only in a part of the area. The above expression also includes a configuration in which the gate electrode is present so as to surround the source electrode or the drain electrode.
[0030] If the gate electrode is arranged between the source electrode and the drain electrode and does not come into contact with the source electrode and the drain electrode, there is no limitation on the width of the gate electrode. From the perspective of the electrode formation process, the width of the gate electrode is preferably 500 nm or more and 10 μm or less. Further, from the perspective of electric field application, the width of the gate electrode is more preferably 500 nm or more and 2 μm or less.
[0031] There is no limitation on the material constituting the gate electrode as long as it is a material with a sufficiently high barrier for the two-dimensional electron gas. As a material satisfying such conditions, it is preferable to include Ni, Au, and at least one of V, Ti, Rh, Pt, Pd, and Al, and particularly preferably an alloy containing Ni and Au.
[0032] 3. Method for manufacturing ultraviolet light receiving element The method for manufacturing an ultraviolet light receiving element according to the present disclosure includes forming a first nitride semiconductor layer containing Al X Ga (1-X) N (0.45 ≦ X ≦ 0.8) on a substrate, and then forming a second nitride semiconductor layer containing Al Y Ga (1-Y) N (X < Y ≦ 1.0) on the first nitride semiconductor layer to form a laminate having the first nitride semiconductor layer and the second nitride semiconductor layer, a trapping level forming step of forming a trapping level in the laminate, and a step of forming a source electrode and a drain electrode on the second nitride semiconductor layer.
[0033] (Laminate formation step) When forming the first nitride semiconductor layer, for example, Al X Ga (1-X) N (0.45 ≦ X ≦ 0.8) is deposited on the substrate using, for example, metalorganic chemical vapor deposition (MOCVD). Also, when forming the second nitride semiconductor layer, in the same manner as when forming the first nitride semiconductor layer, Al Y Ga (1-Y) N (X < Y ≦ 1.0) is deposited on the first nitride semiconductor layer using metalorganic chemical vapor deposition (MOCVD). The first nitride semiconductor layer and the second nitride semiconductor layer can be formed using an Al source such as trimethylaluminum (TMAl), a Ga source such as trimethylgallium (TMGa) or triethylgallium (TEGa), and an N source such as ammonia (NH3).
[0034] (Trapping level formation process) In the trap level formation step, the surface of the second nitride semiconductor layer is etched with plasma or an acidic solution to change the surface state of the laminate, or the laminate is annealed in a high-temperature environment, thereby forming a trap level in the laminate, i.e., in either the first nitride semiconductor layer or the second nitride semiconductor layer.
[0035] When the surface of the second nitride semiconductor layer is etched with plasma to form the trap levels, the trap levels can be formed by inductively coupled plasma (ICP) etching. In this case, for example, BCl3 gas, SF6 gas, Cl2 gas, CF4 gas or the like can be used as the etching gas, and it is preferable to use a mixture of BCl3 gas and SF6 gas. The etching time may be appropriately determined depending on the type of etching gas and etching conditions, but is preferably set to a time sufficient to etch the surface of the second nitride semiconductor layer by approximately 0.5 nm to 2 nm (for example, approximately 100 sec to 300 sec).
[0036] As an example, the surface of the second nitride semiconductor layer can be etched by about 1 nm by etching for 100 seconds while flowing BCl3 gas at 20 sccm and SF6 gas at 10 sccm under conditions of a vacuum degree of 2 Pa, an antenna of 160 W, and a bias of 9 W. At this time, trap levels can be formed due to etching damage on the surface of the second nitride semiconductor layer.
[0037] When the surface of the second nitride semiconductor layer is etched with an acidic solution to form trapping levels, sulfuric acid and hydrogen peroxide solution can be used. In this case, for example, a solution in which sulfuric acid and hydrogen peroxide are mixed in a ratio of 1:2 to 2:1 can be used as the acidic solution. The acidic solution can be used after being heated to, for example, about 60° C. or higher and 100° C. or lower.
[0038] As an example, a solution in which sulfuric acid and hydrogen peroxide are mixed in a 1:1 ratio is heated to 80°C, and the substrate on which the stack is formed is immersed in the solution for 10 minutes. This allows trap levels to be formed in the second nitride semiconductor layer due to surface damage, similar to the case of etching with plasma.
[0039] Furthermore, trap levels can also be formed by annealing the substrate and the laminate in a hydrogen atmosphere. In this case, the substrate on which the stack has been formed is annealed in a hydrogen atmosphere at 900° C. to 1100° C. This causes damage due to atomic deficiencies or the like on the surface or inside of the second nitride semiconductor layer or inside of the first nitride semiconductor layer, and allows trap levels to be formed in the second nitride semiconductor layer or the first nitride semiconductor layer.
[0040] (Electrode formation process) In the electrode formation step, the source electrode and the drain electrode can be formed by various methods, such as by depositing a metal that will be the electrode material on the second nitride semiconductor layer by electron beam deposition (EB) using a resist mask.
[0041] In this case, the source electrode and the drain electrode are preferably formed by depositing V to thicknesses of 10 nm to 30 nm, Al to thicknesses of 70 nm to 90 nm, Mo to thicknesses of 30 nm to 50 nm, and Au to thicknesses of 40 nm to 60 nm, in that order, on the second nitride semiconductor layer, followed by heat treatment. It is also preferable to use Ni to a thickness of 30 nm to 50 nm instead of Mo. The heat treatment is preferably carried out under conditions of, for example, a temperature range of 600° C. to 900° C., a temperature rise rate of 7.5° C. / sec to 20° C. / sec, and a treatment time of 30 seconds to 60 seconds.
[0042] 4. How to measure each component Each of the above-mentioned components of the ultraviolet light receiving element can be measured by the following methods.
[0043] (Method of confirming the elements contained in each layer that composes the UV light receiving element) The elements contained in each layer constituting the ultraviolet light receiving element can be confirmed by energy dispersive X-ray spectroscopy (EDX), X-ray fluorescence analysis (XRF), Rutherford backscattering spectrometry (RBS), secondary ion mass spectrometry (SIMS), and X-ray photoelectron spectroscopy (XPS). The term "each layer" as used herein refers to all components constituting the ultraviolet light receiving element, such as the substrate, the first nitride semiconductor layer, the second nitride semiconductor layer, and the electrodes.
[0044] (Measurement of impurity and doping concentrations) The concentrations of dopants and impurities contained in the substrate and each layer constituting the ultraviolet light receiving element can be measured by secondary ion mass spectrometry (SIMS).
[0045] When measuring the concentration of dopants and impurities in each layer by SIMS after processing into a device, the electrodes can be removed by chemical etching or physical polishing. The concentration of dopants and impurities in each layer can also be measured by sputtering from the substrate side where no electrodes are formed.
[0046] Specifically, SIMS measurements are performed under the measurement conditions provided by Evans Analytical Group (EAG), Inc. A cesium (Cs) ion beam with an energy of 14.5 keV is used to sputter the sample during the measurements.
[0047] (Layer thickness measurement method) The thickness of each layer constituting the ultraviolet light receiving element can be measured by cutting out a predetermined cross section perpendicular to the substrate, observing this cross section with a transmission electron microscope (TEM), and using the length measurement function of the TEM. As a measurement method, first, a cross section perpendicular to the main surface of the substrate of the ultraviolet light receiving element (for example, a-plane) is observed using a TEM. Specifically, for example, in a TEM image showing a cross section perpendicular to the main surface of the substrate of the ultraviolet light receiving element, a range of 2 μm or more in a direction parallel to the main surface of the substrate is set as the observation width. Since contrast is observed at the interface between two layers with different compositions within this observation width, the thickness up to this interface is observed in a continuous observation region with a width of 200 nm. The average value of the thickness of each layer included in this 200 nm wide observation region can be calculated from five points arbitrarily extracted from the above-mentioned observation width of 2 μm or more, to obtain the layer thickness of each layer.
[0048] (Method of measuring the Al composition of the first nitride semiconductor layer) The Al composition of the first nitride semiconductor layer can be measured by reciprocal space mapping (RSM) using X-ray diffraction (XRD). Specifically, the lattice relaxation rate relative to the underlayer and the Al composition can be obtained by analyzing reciprocal space mapping data in the vicinity of a diffraction peak obtained with an asymmetric plane as a diffraction plane. Examples of the diffraction plane include the (10-15) plane and the (30-24) plane.
[0049] (Method of measuring the Al composition of the second nitride semiconductor layer) The Al composition of the second nitride semiconductor layer can be measured by X-ray photoelectron spectroscopy (XPS), energy dispersive X-ray spectroscopy (EDX), and electron energy-loss spectroscopy (EELS).
[0050] In EELS, the composition of a sample is analyzed by measuring the energy lost when an electron beam passes through the sample. Specifically, for example, the energy loss spectrum of the intensity of the transmitted electron beam is measured and analyzed for a thin-sectioned sample used in TEM observation. The position of the peak that appears around 20 eV of energy loss changes depending on the composition of each layer, and the composition can be determined from the peak position.
[0051] In EELS, the Al composition of each layer is obtained by calculating the average value of the Al composition in an observation width of 200 nm from five points arbitrarily selected from an observation region of 2 μm or more, in the same manner as in the layer thickness calculation method by TEM observation described above.
[0052] In EDX, characteristic X-rays generated by an electron beam in a thin-sectioned sample used in the above-mentioned TEM observation, etc. are measured and analyzed. In EDX, the Al composition of each layer is obtained by calculating the average value of the Al composition in an observation width of 200 nm from five points arbitrarily selected from an observation region of 2 μm or more, in the same way as in the layer thickness calculation method using TEM observation described above.
[0053] XPS allows the evaluation of the composition in the depth direction by performing sputter etching using an ion beam while performing XPS measurement. The ion beam is generally Ar + However, other ion species such as Ar cluster ions may be used as long as they can be irradiated with the etching ion gun mounted on the XPS device. The XPS peak intensities of Al, Ga, and N are measured and analyzed to obtain the depth profile of the Al composition in each layer. Instead of sputter etching, the ultraviolet light receiving element may be polished obliquely so that a cross section perpendicular to the main surface of the substrate is enlarged and exposed, and the exposed cross section may be measured by XPS.
[0054] The composition of each layer can be measured not only by XPS but also by Auger Electron Spectroscopy (AES). In this case, the composition can be measured by Auger Electron Spectroscopy on a cross section exposed by sputter etching or oblique polishing. The composition of each layer can also be measured by SEM-EDX measurement of a cross section exposed by oblique polishing.
[0055] (Method of measuring capture level) The trap level can be calculated from the irradiation intensity dependency of the UV light receiving element. Specifically, the irradiation intensity of the UV light that the UV light receiving element reacts to is 1 nW / cm 2 ~100nW / cm 2 The voltage is varied from 0 V to 1 V. At this time, a constant voltage (for example, 5 V) is applied between the source and drain, and the current flowing between the source and drain electrodes is measured versus time. Note that accurate current and voltage measurements can be made using a parameter analyzer and a probe measuring device. The time from irradiation with UV light until the current saturates is defined as the saturation time (ΔT). The number of photons (Pc) contained in the irradiated light can be calculated from the wavelength and irradiation intensity of the UV light. The product of ΔT and Pc mentioned above can be approximated as the trap level density. 1nW / cm 2 ~100nW / cm 2 Measurements are performed at 10 points within the range of 100 nm, and the average of the trap level densities calculated by the above method is taken as the trap level density. If a measurement point appears whose trap level density is more than 5 times different from the median value of the 10 points, that point is excluded and the average value of the remaining points is taken as the trap level density.
[0056] 5. Specific configuration of ultraviolet light receiving element Below, a first example of a specific configuration of an ultraviolet light receiving element according to the present disclosure, an ultraviolet light receiving element 1, a second example, an ultraviolet light receiving element 2, and a third example, an ultraviolet light receiving element 3, will be described with reference to Figures 1 to 3, respectively. The ultraviolet light receiving elements 1, 2, and 3 are semiconductor elements capable of receiving ultraviolet light.
[0057] <First Example> As shown in Fig. 1, the ultraviolet light receiving element 1, which is the first example, includes a substrate 11, a first nitride semiconductor layer 12, a second nitride semiconductor layer 13, a source electrode 14, and a drain electrode 15. The first nitride semiconductor layer 12 is disposed on the substrate 11 and contains Al X Ga (1-X) N (0.45 ≦ X ≦ 0.8). The second nitride semiconductor layer 13 is disposed on the first nitride semiconductor layer and contains Al Y Ga (1-Y) N (X < Y ≦ 1). The first nitride semiconductor layer 12 and the second nitride semiconductor layer 13 constitute a laminate 16. Either the laminate 16, that is, the first nitride semiconductor layer 12 or the second nitride semiconductor layer 13, has a trap level density of 1.0×10 11 cm -2 or more and 1.0×10 14 cm -2 or less. The source electrode 14 and the drain electrode 15 are arranged with a width W.
[0058] <Second Example> As shown in Fig. 2, the ultraviolet light receiving element 2, which is the second example, includes a substrate 11, a buffer layer 27, a first nitride semiconductor layer 12, a second nitride semiconductor layer 13, a source electrode 14, and a drain electrode 15. The ultraviolet light receiving element 2 is different from the ultraviolet light receiving element 1 of the first example in that it includes a buffer layer 27. Hereinafter, the buffer layer 27 will be described.
[0059] (Buffer Layer) The buffer layer 27 is formed between the substrate 11 and the first nitride semiconductor layer 12, and is preferably formed over the entire surface of the substrate 11. By providing the buffer layer 27, a nitride semiconductor layer with a small lattice constant difference, a small coefficient of thermal expansion difference, and few defects is formed on the buffer layer 27. Further, by providing the buffer layer 27, the first nitride semiconductor layer 12 can be grown under compressive stress, and the occurrence of cracks in the first nitride semiconductor layer 12 can be suppressed. Therefore, even when the substrate 11 is formed of a nitride semiconductor such as AlN or AlGaN, a nitride semiconductor layer with few defects can be formed above the buffer layer 27.
[0060] The buffer layer 27 is formed of a nitride semiconductor such as AlN or AlGaN, etc. The buffer layer 27 may contain impurities such as C, Si, Fe, Mg, etc.
[0061] The buffer layer 27 has a thickness of, for example, several μm. Specifically, the thickness of the buffer layer 27 is preferably thicker than 10 nm and thinner than 10 μm. When the thickness of the buffer layer 27 is thicker than 10 nm, the crystallinity of the nitride semiconductor such as AlN is high. When the thickness of the buffer layer 27 is thinner than 10 μm, cracks are less likely to occur in the buffer layer 27 formed by crystal growth on the entire surface of the wafer. Moreover, the buffer layer 27 is more preferably thicker than 50 nm and thinner than 5 μm. When the thickness of the buffer layer 27 is thicker than 50 nm, a layer with high crystallinity can be formed. When the thickness of the buffer layer 27 is thinner than 5 μm, cracks are less likely to occur in the buffer layer 27.
[0062] <Third Example> 3, the ultraviolet light receiving element 3 as the third example includes a substrate 11, a first nitride semiconductor layer 12, a second nitride semiconductor layer 13, a source electrode 14, a drain electrode 15, and a surface protection layer 38. The ultraviolet light receiving element 2 differs from the ultraviolet light receiving element 1 in that it includes the surface protection layer 38. The surface protective layer 38 will now be described.
[0063] (Surface protective layer) The surface protective layer 38 is formed so as to cover the entire surface of the second nitride semiconductor layer 13. In this case, the surface protective layer 38 may be present also on the source electrode 14 and the drain electrode 15, as long as each of the source electrode 14 and the drain electrode 15 is partially exposed. By providing the surface protective layer 38, the ultraviolet light receiving element 2 can be protected from deterioration due to humidity and heat. The surface protection layer 38 is made of, for example, SiO2, SiN, Al2O3, AlN or the like.
[0064] The ultraviolet light receiving element 3 is characterized in that it is provided with a surface protection layer 38. Fig. 3 shows a configuration in which the ultraviolet light receiving element 1, which is a first example of the ultraviolet light receiving element 3, is provided with the surface protection layer 38, but it may also be a configuration in which the ultraviolet light receiving element 2, which is a second example, is provided with the surface protection layer 38. EXAMPLES
[0065] Examples and comparative examples of the present invention will be described below.
[0066] [Example 1] A buffer layer (hereafter referred to as the AlN layer) was formed on a 2-inch sapphire wafer by growing 1 μm of AlN using metal organic deposition while maintaining the surface temperature of the substrate at 1250°C. Next, while maintaining the surface temperature of the AlN layer at 1050°C, Al X Ga (1-X) A first nitride semiconductor layer was formed by growing 150 nm of AlN (X=0.50) on the first nitride semiconductor layer while keeping the surface temperature of the first nitride semiconductor layer at 1050° C. Y Ga (1-Y) N (Y=0.60) was grown to a thickness of 25 nm to form a second nitride semiconductor layer.
[0067] In this state, the carrier concentration of the two-dimensional electron gas induced at the interface between the first and second nitride semiconductor layers was calculated using simulation software and found to be 1×10 12 cm -2 It was.
[0068] Next, the substrate on which the first and second nitride semiconductor layers were formed was cleaned, and a resist mask having a plurality of openings of 450 μm×450 μm was formed on the second nitride semiconductor layer. Next, etching was performed using an inductively coupled plasma (ICP) etching device through this resist mask to perform mesa separation, thereby electrically insulating the plurality of elements formed on the wafer from each other.
[0069] Next, after removing the resist mask, etching was performed for 100 seconds in an ICP etching apparatus under conditions of a vacuum degree of 2.0 Pa, an antenna of 160 W, and a bias of 9 W while flowing BCl3 gas at 20 sccm and SF6 gas at 10 sccm to form a trap level.
[0070] Next, for each element, source and drain electrodes were formed on the second nitride semiconductor layer at intervals of 5 μm by EB deposition. The source and drain electrodes were formed by depositing V, Al, Mo, and Au in this order from the second nitride semiconductor layer side. At this time, the film thicknesses of each layer were V: 20 nm, Al: 80 nm, Mo: 50 nm, and Au: 40 nm.
[0071] Next, the resist mask was removed, and an annealing process was performed in which the temperature was raised to 700°C in 40 seconds using an infrared lamp annealing device, then held for 30 seconds, and then cooled. This resulted in the formation of source and drain electrodes made of an alloy containing V, Al, Mo, and Au. Next, the sapphire wafer was diced to obtain multiple ultraviolet light receiving elements.
[0072] The characteristics of the obtained ultraviolet light receiving element were measured by the following method. [Measurement of photocurrent and dark current values] A simulated sunlight source was used as the light source, and a spectroscope was also used. The upper surface of the second nitride semiconductor layer was irradiated with ultraviolet light having a wavelength of 250 nm and an intensity of 10 μW / cm. 2 The current flowing between the source and drain electrodes was measured when the device was irradiated with UV light and the source-drain voltage was set to 5 V. The current flowing in a dark state without UV light irradiation (dark current) was also measured at a source-drain voltage of 5 V. A parameter analyzer and a probe measuring instrument were used to measure the current and voltage.
[0073] As a result of the measurement, the dark current was 1.0×10 -10 A / mm, and the photocurrent is 7.0×10 -5 The photosensitivity obtained by converting the photocurrent was 7.0×10 4The ratio of the photocurrent value (current value when irradiated with ultraviolet light of wavelength 250 nm) to the dark current value obtained, S / N (photocurrent / dark current), was 7.0 × 10 5 At this time, the irradiation intensity of ultraviolet light was 1, 2, 5, 7, 10, 20, 30, 50, 70, and 100 nW / cm 2 The time to saturation of the photocurrent was measured while changing the 11 cm -2 It was.
[0074] [Example 2] An ultraviolet light emitting device was obtained in the same manner as in Example 1, except that the etching time during ICP etching was changed to 150 seconds to form a trap level. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 12 cm -2 In each of the examples and comparative examples from Example 2 onwards, the values of photocurrent and dark current, and the light sensitivity are shown in Table 1 which will be described later.
[0075] [Example 3] An ultraviolet light emitting device was obtained in the same manner as in Example 1, except that the etching time during ICP etching was changed to 200 seconds to form a trap level. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0076] [Example 4] An ultraviolet light emitting device was obtained in the same manner as in Example 1, except that the etching time during ICP etching was changed to 300 seconds to form a trap level. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 14 cm -2 It was.
[0077] [Example 5] Except for forming trapping levels by performing etching using an acidic solution instead of an ICP etching device, an ultraviolet light-emitting device was obtained in the same manner as in Example 1. At this time, a solution in which sulfuric acid and hydrogen peroxide were mixed in a ratio of 1:1 was used as the acidic solution, and the acidic solution was heated to 80° C., and the substrate on which the first nitride semiconductor layer and the second nitride semiconductor layer were formed was immersed in the solution for 10 minutes to perform etching. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 12 cm -2 It was.
[0078] [Example 6] An ultraviolet light emitting device was obtained in the same manner as in Example 5, except that the acid solution used in the etching with the acid solution was heated to 100° C. to form a trap level. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0079] [Example 7] Except for forming trap levels by performing annealing instead of ICP etching, an ultraviolet light emitting device was obtained in the same manner as in Example 1. At this time, the substrate on which the first nitride semiconductor layer and the second nitride semiconductor layer were formed was annealed at 1000° C. in a hydrogen atmosphere. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 12 cm -2 It was.
[0080] [Example 8] An ultraviolet light emitting device was obtained in the same manner as in Example 7, except that the annealing temperature condition was changed to 1100° C. to form a trap level. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0081] [Example 9] An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that the substrate was changed to an AlN substrate and the thickness of the buffer layer was changed to 0.5 μm. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0082] [Example 10] An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that the distance between the source electrode and the drain electrode was set to 2 μm. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0083] [Example 11] An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that the distance between the source electrode and the drain electrode was set to 10 μm. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0084] [Example 12] An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that the distance between the source electrode and the drain electrode was set to 20 μm. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0085] [Example 13] An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that the distance between the source electrode and the drain electrode was set to 30 μm. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2It was.
[0086] [Example 14] The first nitride semiconductor layer is Al X Ga (1-X) N (X=0.60), and the second nitride semiconductor layer is Al Y Ga (1-Y) An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that it was formed of N (Y=0.70). The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0087] [Example 15] The first nitride semiconductor layer is Al X Ga (1-X) N (X=0.70), and the second nitride semiconductor layer is Al Y Ga (1-Y) An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that it was formed of N (Y=0.80). The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0088] [Example 16] The first nitride semiconductor layer is Al X Ga (1-X) N (X=0.80), and the second nitride semiconductor layer is Al Y Ga (1-Y) An ultraviolet light emitting device was obtained in the same manner as in Example 3, except that it was formed of N (Y=0.90). The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0089] [Example 17] An ultraviolet light-emitting device was obtained in the same manner as in Example 3, except that the distance between the source electrode and the drain electrode was 10 μm, and a gate electrode having a gate width of 2 μm was provided between the source electrode and the drain electrode by depositing Ni: 10 nm and Au: 40 nm in that order from the second nitride semiconductor layer side. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 13 cm -2 It was.
[0090] [Comparative Example 1] An ultraviolet light emitting device was obtained in the same manner as in Example 1, except that ICP etching was not performed and trap levels were not formed. The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the trap level density was estimated to be 1.0×10 8 cm -2 It was.
[0091] [Comparative Example 2] The first nitride semiconductor layer is Al X Ga (1-X) N (X=0.40), and the second nitride semiconductor layer is Al Y Ga (1-Y) An ultraviolet light emitting device was obtained in the same manner as in Example 1, except that it was formed of N (Y=0.50). The characteristics of the obtained UV light receiving element were measured in the same manner as in Example 1, but the photocurrent was not different from the dark current, and it was impossible to estimate the time until saturation. Therefore, it was impossible to estimate the trap level density.
[0092] [Comparative Example 3] The first nitride semiconductor layer is Al X Ga (1-X) N (X=0.90), and the second nitride semiconductor layer is Al Y Ga (1-Y) An ultraviolet light emitting device was obtained in the same manner as in Example 1, except that it was formed of N (Y=1.0). The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1. However, there was no difference between the photocurrent and the dark current, and it was impossible to estimate the time until saturation. Therefore, the density of the trapping level could not be estimated.
[0093] [Comparative Example 4] An ultraviolet light emitting element was obtained in the same manner as in Example 1, except that the second nitride semiconductor layer was formed of Al Y Ga (1-Y) N (Y = 0.40). The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1. However, there was no difference between the photocurrent and the dark current, and it was impossible to estimate the time until saturation. Therefore, the density of the trapping level could not be estimated.
[0094] [Comparative Example 5] An ultraviolet light emitting element was obtained in the same manner as in Example 1, except that the second nitride semiconductor layer was formed of Al Y Ga (1-Y) N (Y = 0.50). The characteristics of the obtained ultraviolet light receiving element were measured in the same manner as in Example 1, and the density of the trapping level was estimated. As a result, it was 1.0 × 10 12 cm -2 .
[0095] The evaluation results of each example and comparative example are shown in Table 1 below. In Table 1, "V / Al / Mo / Au" indicates that V, Al, Mo, and Au are laminated in this order from the side of the second nitride semiconductor layer.
[0096]
Table 1
[0097] As shown in Table 1, a laminate including a first nitride semiconductor layer formed of Al X Ga (1-X) N (0.45 ≤ X ≤ 0.8) and a second nitride semiconductor layer formed of Al Y Ga (1-Y) N (X < Y ≤ 1.0) was irradiated with 1.0 × 10 11 cm-2 Above 1.0×10 14 cm -2 For each ultraviolet light receiving element in which the following capture levels were formed, a high S / N (the ratio of the value of photocurrent to the value of dark current) was obtained.
[0098] On the other hand, for the ultraviolet light receiving element of Comparative Example 1 in which the capture levels above 1.0×10 11 cm -2 above and below 1.0×10 14 cm -2 were not formed, both the light reception sensitivity and the ratio S / N of the value of photocurrent to the value of dark current were low. This is because the increase in photocurrent due to the capture level could not be obtained, and a current other than the photocurrent due to the two-dimensional electron gas could not be obtained.
[0099] Further, when the Al composition ratio X in the first nitride semiconductor layer is outside the range of 0.45 or more and 0.8 or less, no current flows through the ultraviolet light receiving element because relaxation of the second nitride semiconductor layer (Comparative Example 2) or contact cannot be made (Comparative Example 3). Further, when the Al composition ratio Y in the second nitride semiconductor layer does not satisfy X < Y ≦ 1.0, a two-dimensional hole gas is generated instead of the two-dimensional electron gas and no current flows through the ultraviolet light receiving element (Comparative Example 4), or the two-dimensional electron gas is not generated and the current through the two-dimensional electron gas is suppressed (Comparative Example 5). Therefore, when the Al composition ratios of the first nitride semiconductor layer and the second nitride semiconductor layer are not in the preferable range, both the light reception sensitivity and the ratio S / N of the value of photocurrent to the value of dark current are low.
[0100] From the above, it has been found that it is necessary to appropriately set the Al composition ratios of the first nitride semiconductor layer and the second nitride semiconductor layer and the density of the capture levels.
[0101] Although the embodiments of the present invention have been described above, the technical scope of the present invention is not limited to the technical scope described in the above embodiments. It is clear from the description of the claims that various changes or improvements can be made to the above-described embodiments, and forms with such changes or improvements can also be included in the technical scope of the present invention.
Description of Reference Numerals
[0102] 11 Substrate 12 First nitride semiconductor layer 13 Second nitride semiconductor layer 14 Source electrode 15 Drain electrode 16 Laminate 27 Buffer Layer 38 Surface protective layer
Claims
1. Al on the substrate X G (1-X) After forming a first nitride semiconductor layer containing N (0.45≦X≦0.8), Al is deposited on the first nitride semiconductor layer. Y G (1-Y) a stacking step of forming a second nitride semiconductor layer containing N (X<Y≦1.0) to form a stacking step having the first nitride semiconductor layer and the second nitride semiconductor layer; The surface of the second nitride semiconductor layer is treated with BCl 3 Gas and SF 6 By performing plasma etching for 200 to 300 seconds using a mixed gas of 1.0×10 13 cm -2 Above 1.0 x 10 14 cm -2 A capture level forming step of forming a capture level as follows: an electrode forming step of forming a source electrode and a drain electrode on the second nitride semiconductor layer by vapor deposition; A method for manufacturing an ultraviolet light receiving element comprising the steps of:
2. Al on the substrate X G (1-X) After forming a first nitride semiconductor layer containing N (0.45≦X≦0.8), Al is deposited on the first nitride semiconductor layer. Y G (1-Y) a stacking step of forming a second nitride semiconductor layer containing N (X<Y≦1.0) to form a stacking step having the first nitride semiconductor layer and the second nitride semiconductor layer; The surface of the second nitride semiconductor layer is etched by immersing it in an acidic solution of sulfuric acid and hydrogen peroxide in a ratio of 1:2 to 2:1 at 100° C. for 10 minutes. 13 cm -2 Above 1.0 x 10 14 cm -2 A capture level forming step of forming a capture level as follows: an electrode forming step of forming a source electrode and a drain electrode on the second nitride semiconductor layer by vapor deposition; A method for manufacturing an ultraviolet light receiving element comprising the steps of:
3. Al on the substrate X G (1-X) After forming a first nitride semiconductor layer containing N (0.45≦X≦0.8), Al is deposited on the first nitride semiconductor layer. Y G (1-Y) a stacking step of forming a second nitride semiconductor layer containing N (X<Y≦1.0) to form a stacking step having the first nitride semiconductor layer and the second nitride semiconductor layer; The substrate and the laminate were annealed at 1100° C. in a hydrogen atmosphere to form a nitride semiconductor layer having a density of 1.0×10 13 cm -2 Above 1.0 x 10 14 cm -2 A capture level forming step of forming a capture level as follows: an electrode forming step of forming a source electrode and a drain electrode on the second nitride semiconductor layer by vapor deposition; A method for manufacturing an ultraviolet light receiving element comprising the steps of:
Citation Information
Patent Citations
High-detectivity gallium-nitride-based Schottky ultraviolet detector using graphene
CN104393093A
A double heterojunction ultraviolet detector
CN109065663A
Decrease of surface defects in semiconductor material having volatile chemical species
JP1998261592A
GaN SYSTEM SEMICONDUCTOR LIGHT RECEIVING ELEMENT
JP2003086825A
Nitride semiconductor device
JP2008205029A